Investigation of Stress Levels according to the Exercise Behavior Change Stages of Women - Cetin, Semra; Imamoglu, Osman (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to investigate the stress levels according to the exercise behavior change stages of sedentary women. Methods: Four hundred and sixty sedentary women who completed the surveys in Sakarya were included in the study. Perceived stress level and change in exercise behavior survey were applied. One-way ANOVA, LSD test, and independent sample t test were used in the study. Results: The mean age of sedentary women were 31.59 years. The health status of sedentary women was founded with19.78% very good, 44.78% good, 24.35% middle, and 11.9% bad. Sedentary women’s stress points were found to be 29.33 points for those with good health and 36.00 points for those with bad ones. Sedentary women’s stress scores were 31.84 before the trend, they were 28.03 in the continuity phase. In sedentary women, the stress scores of the pre-trend and post-shift stages were significantly higher than those of the exercise and behavioral stages (p<0.05). Stress scores of participants in regular physical activity for the last 6 months and 3 years were found to be lower than those who did not participate (p <0.05). Conclusion: The perceived stress levels of sedentary women according to their exercise behavior change stages were high before the tendency and low during the exercise during continuity. Sedentary women should increase the percentage of continuity in exercise behaviors steps to reduce perceived stress levels. Stress level according to exercise behavior change stages should be investigated in a large number of sedentary women in different regions in Turkey and they should be trained on exercise planning.